2019
DOI: 10.1002/jcb.28655
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of a competing endogenous RNA network reveals key long noncoding RNAs as potential prognostic biomarkers for hepatocellular carcinoma

Abstract: Growing evidence has revealed that long noncoding RNAs (lncRNAs) have an important impact on tumorigenesis and tumor progression via a mechanism involving competing endogenous RNAs (ceRNAs). However, their use in predicting the survival of a patient with hepatocellular carcinoma (HCC) remains unclear. The aim of this study was to develop a novel lncRNA expression-based risk score system to accurately predict the survival of patients with HCC. In our study, using expression profiles downloaded from The Cancer G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…It was originally reported in the Mammalian Gene Collection project of the National Institutes of Health, with the purpose of identifying putative alternative promoters for human genes, but no detailed study is yet available [ 5 , 6 ]. Recently, an overall survival (OS) risk scoring system for HCC patients has been constructed based on the expression of 6 lncRNAs including MYLK-AS1 [ 7 ]. According to reports, MYLK-AS1 promotes the growth and invasion of HCC through the EGFR/HER2-ERK1/2 signaling pathway [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was originally reported in the Mammalian Gene Collection project of the National Institutes of Health, with the purpose of identifying putative alternative promoters for human genes, but no detailed study is yet available [ 5 , 6 ]. Recently, an overall survival (OS) risk scoring system for HCC patients has been constructed based on the expression of 6 lncRNAs including MYLK-AS1 [ 7 ]. According to reports, MYLK-AS1 promotes the growth and invasion of HCC through the EGFR/HER2-ERK1/2 signaling pathway [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…28 The previous reports have suggested a controversial role of PART1 in cancers. For instance, Hu et al found that PART1 was overexpressed in bladder cancer specimens and silencing of PART1 led to cell proliferation inhibition and apoptosis in bladder cancer cells; 29 data mining of TCGA dataset revealed that higher expression of PART1 was associated with a higher risk of recurrence for patients with hepatocellular carcinoma; 30 in oral squamous cell carcinoma, however, patients with higher expression of PART1 exhibited longer overall survival compared with patients with lower expression of PART1. 31 Although one study indicated that higher expression of PART1 was associated with longer survival in patients with GBM, 32 the role and molecular mechanisms of PART1 in glioma are not known.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies constructed risk scoring systems to predict the prognosis of HCC patients (Gu et al, 2018;Liao et al, 2018;Ma et al, 2018;Shi et al, 2018;Sui et al, 2018;Wu et al, 2018b;Zhao et al, 2018;Bai et al, 2019;Yan et al, 2019;Ye et al, 2019;Zhang et al, 2019). However, all these risk scoring systems are based on lncRNAs differentially expressed between HCC and normal samples, while our systems are based on lncRNAs differentially expressed between HCC patients with or without cirrhosis.…”
Section: Discussionmentioning
confidence: 99%